Evaluation for Color Matching of Single Shade and Multi Shade Composite with Enamel before and after Home Bleaching (A Comparative In-vitro Study) - الياسين, محمود; منذر حداد , (Latakia University Journal -Medical Sciences Series, 2024)
Objective: To investigate the effect of home bleaching on color matching between two type of dental restoration materials and the adjacent tooth structure. Material and Methods: 40 intact premolars were used. After preparation, the teeth were restored with single shade composite resin (Group A), and conventional composite resin (Group B) (n=20). After that, the bleaching process was performed for 14 days. The color matching was investigated before and after the bleaching process. Paired t-test was employed to compare the color of the intact tooth and the dental restoration before and after the bleaching processes. The level of significance was set at 5%. Results: The specimens restored with conventional composite resin exhibited a significant change in color matching after home bleaching (P < 0.05). However, non-significant reduction in color matching observed in specimens restored with single shade composite resin (P > 0.05). Conclusion: The home bleaching processes had a significant effect on the discoloration of the conventional dental restoration; however, the application of single shade composite resin improved the tooth composite color-match after home bleaching.